State Capacity, National Economic Policies and Local Development: The Russian State in the Southern Urals - Gerda Asmus; Raphaël Franck (Center for Economic Studies and ifo Institute (CESifo), 2022)
This study analyzes how state capacity shapes the local impact of national policies by exploiting a quasi-natural experiment in the regional expansion of the state. It uses the local discontinuity created by the boundary of the largest peasant rebellion in 18th century Russia where the state increased security forces and levied taxes more efficiently after the uprising ended. The results show that increased state capacity had limited effects on economic growth until the central government targeted specific development objectives. Namely, when rulers chose to build schools or foster industrialization, their national policies benefited areas which already had strong state capacity.
Keywords: O11; O43; N13; N14; 330; economic growth; public policies; Russia; state capacity